Comparison of the predatory rotifers Pleurotrocha petromyzon (Ehrenberg, 1830) and Pleurotrocha sigmoidea Skorikov, 1896 (Rotifera: Monogononta: Notommatidae) based on light and electron microscopic observations - Wilts, Eike F.; Bininda-Emonds, Olaf R. P.; Ahlrichs, Wilko H. (Zootaxa, 2009)
In the course of phylogenetic investigations across Rotifera, we reinvestigated Proales sigmoidea (Skorikov, 1896) and found significant similarities with respect to its morphology, ecology and behaviour to Pleurotrocha petromyzon (Ehrenberg, 1830). Both species feed on stalked ciliates and show a similar habitus as well as similar virgate trophi. We here present new morphological details for both species based on light and electron micrographs. In light of our results, we suggest the reassignment of Proales sigmoidea to Pleurotrocha Ehrenberg, 1830. To further support our case, we provide additional comparisons with other species of the latter genus, including Pleurotrocha robusta (Glasscott, 1893), for which we present additional information.